2004
DOI: 10.1002/ab.20017
|View full text |Cite
|
Sign up to set email alerts
|

Nature, extent, and causes of bullying among personality‐disordered patients in a high‐secure hospital

Abstract: The present study explored the perceptions and experiences of the nature, extent and causes of bullying among personality-disordered patients, with a subsidiary aim of exploring differences in perceptions between staff and patients. The sample was selected from the Personality Disorder Unit of a high secure hospital. The total sample consisted of 60 participants, 30 patients and 30 staff. Participants engaged in a semi-structured interview based on that developed by Brookes [1993] and modified by Ireland and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
53
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 26 publications
9
53
2
Order By: Relevance
“…To date, research within psychiatric settings has focused on personality-disordered populations. The studies of Ireland [2004Ireland [ , 2005 were related studies sampling adult male personality-disordered offenders detained within a high-secure psychiatric hospital. The first study focused on the nature and extent of bullying and the second on the perceptions and definitions of bullying.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, research within psychiatric settings has focused on personality-disordered populations. The studies of Ireland [2004Ireland [ , 2005 were related studies sampling adult male personality-disordered offenders detained within a high-secure psychiatric hospital. The first study focused on the nature and extent of bullying and the second on the perceptions and definitions of bullying.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 60 interviews were conducted involving 30 staff and 30 patients. Ireland [2004] reported that one fifth of patients and staff reported they had seen a patient being bullied in the previous week. One fifth of patients reported being bullied in the previous week, with less than one tenth reporting to have bullied others.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations